The Effect of Baby-Led Weaning and Traditional Complementary Feeding Trainings on Baby Development: Study Protocol - Nurten Arslan; Meltem Kürtüncü; Pınar Menderes Turhan (Hemşirelikte Araştırma Geliştirme Dergisi)

(untitled)
Aim: In this study, it was aimed to evaluate the risks of self-feeding, transition to early solids and home meals, choking, anemia and obesity in 6-and 12-month-old infants who were introduced to complementary feeding with the trainings of traditional complementary feeding (TCF) and baby-led weaning (BLW) methods.Material and Method: This study is an experimental and randomized controlled study conducted to examine the effect of the trainings of the TCF and BLW methods on the transition to complementary feeding. The population of the study consisted of 73 infants aged 4 and 5 months who 62 were assigned to intervention groups by stratified randomization method. The study was conducted according to the CONSORT-2010 checklist. Five complementary feeding modular trainings with 8 sessions, appropriate for the age of the baby in months, were carried out in both intervention groups. In both groups, the trainings were maintained until the baby was 4 months to 12 months old. The outcomes consisted of height, weight gain, LAZ (Length for age z-score), WAZ (Weight for age z-score), and WLZ (Weight for length z-score) scores at 12 months, iron intake, hemoglobin, hematocrit, and ferritin levels, micronutrients, choking risk, growth retardation, transition time to solid foods, family meals and self-feeding, behaviors of transition to complementary feeding and developmental assessment parameters.Practice Implications: This study, the trainings given are expected to give an idea about the extent to which they affect the infant's body weight, growth and development, iron and micronutrient intake, obesity, choking and growth retardation risks..